Carcinoma en cuirasse: Reason for Initial Consultation in a Breast Cancer (2019)
ABSTRACT: Breast cancer in women represents the fifth cause of death in the world and the leading cause of cancer death in Colombia. Cutaneous metastases of this cancer are frequent, 23.9% of the cases, and 3% of them present as a carcinoma in cuirasse with papules and nodules, initially dispersed, which are later grouped into scleroderma-like lesions; Keloid-like lesions are rare. We present the case of a 56-year-old woman with a breast metastasis of a mammary carcinoma with pruritic lesions similar to keloids, from which a hidden breast cancer was diagnosed. In skin histopathology, a fibrotic stroma was found with atypical cells that infiltrated collagen bundles in an "Indian row" pattern, positive for estrogen and progestogen hormone receptors. The patient presented a clinical improvement of skin lesions and symptoms after chemotherapy. The clinical diversity of skin metastases and the importance of suspecting breast cancer from keloid lesions in the anterior thorax are highlighted.